Becoming Language Teacher-Researchers in a Research Seedbed - Claudia Patricia Mesa Villa; John S. Gómez-Giraldo; Rodolfo Arango Montes (Universidad Nacional de Colombia, 2020)
In this paper, a teacher-educator and two students of a B.A. program in foreign language teaching (English and French) of a public university in Colombia discuss our pedagogical experiences in a research seedbed. First, we present the conceptualizations underlying our analysis: research seedbeds, undergraduate research education, and curriculum as a process. Second, we describe our contextual background. Third, we analyze our experiences using three themes: creating and recreating curriculum, negotiating the official and non-official curriculum, and taking positions as teacher-researchers. We conclude that research seedbeds can broaden the pedagogical repertoire of undergraduate research education in foreign language programs and that it becomes necessary to conduct studies in this area in Colombia.